2009
DOI: 10.1002/bit.22553
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure systems for gas‐phase free continuous incubation of enriched marine microbial communities performing anaerobic oxidation of methane

Abstract: Novel high-pressure biotechnical systems that were developed and applied for the study of anaerobic oxidation of methane (AOM) are described. The systems, referred to as high-pressure continuous incubation system (HP-CI system) and high-pressure manifold-incubation system (HP-MI system), allow for batch, fed-batch, and continuous gas-phase free incubation at high concentrations of dissolved methane and were designed to meet specific demands for studying environmental regulation and kinetics as well as for enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…The SR rate of sediment from Hydrate Ridge was significantly higher at an elevated CH 4 partial pressure (1,2). At between 0 and 0.15 MPa, there was a positive linear correlation between the CH 4 partial pressure and the AOM and SR rates of an anaerobic methanotrophic enrichment obtained from Eckernförde Bay sediment (3).…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…The SR rate of sediment from Hydrate Ridge was significantly higher at an elevated CH 4 partial pressure (1,2). At between 0 and 0.15 MPa, there was a positive linear correlation between the CH 4 partial pressure and the AOM and SR rates of an anaerobic methanotrophic enrichment obtained from Eckernförde Bay sediment (3).…”
mentioning
confidence: 91%
“…The rate of methane-dependent sulfide production by microbial mats from the Black Sea increased 10-to 15-fold after the methane partial pressure was increased from 0.2 to 10.0 MPa (4). The affinity constant for methane (K m ) of anaerobic methanotrophs from Gulf of Cádiz sediment is about 37 mM, which is equivalent to 3 MPa CH 4 (5). Because of the more negative Gibbs free energy change (⌬G) at elevated CH 4 partial pressures, the growth of anaerobic methanotrophs might be faster when the CH 4 partial pressure is increased (see Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although, high pressure bioreactors might not be practical for waste water treatment, they might be ideal to grow sludge as long as a high methane partial pressure can be combined with biomass retention and sulfide removal. Deusner et al (2009) demonstrated AOM in continuous high pressure bioreactors.…”
Section: Other Incubation Techniquesmentioning
confidence: 99%